Retrospective analysis: The application of human menopausal gonadotropin combined with letrozole for IUI in patients undergoing artificial insemination by husband due to unexplained or mild male factors - Li, Hua-qing; Pan, Xin-ling; Su, Nian-jun; Lu, Xi-ping; Chen, Jun-qing; Chen, Xu-wei (Frontiers in Endocrinology, 2022)
Objective: To compare the effects of human menopausal gonadotropin (HMG) plus letrozole (LE) to HMG only for ovarian stimulation on pregnancy outcome of infertile patients undergoing artificial insemination by husband (AIH) due to unexplained or mild male factors. Results: In total,526 cycles of 372 couples were included. The univariable analysis showed that the clinical pregnancy rate of the HMG combined with LE group was 24.8%, significantly higher than that of the HMG group (14.8%, P = 0.007). The live birth rate (19.9%) of the HMG combined with LE group were also significantly higher than those of the HMG group (11.2%, respectively). In multivariable logistic analysis, male age was negatively associated with clinical pregnancy rate (OR 0.9, 95% CI 0.82~0.98, P=0.014) and live birth (OR 0.91, 95% CI 0.82~1.0, P=0.051). For live birth, the only significant fact was ovary stimulation, with HMG+LE group owning a higher of live birth rate comparing to HMG only (OR 2.05, 95% CI 1.14~3.7, P= 0.017). Conclusion: The ovarian stimulation using HMG+LE could increase the final clinical outcome (live birth) among infertile patients undergoing AIH due to explained or mild male factors.